2021
DOI: 10.1186/s13019-021-01556-1
|View full text |Cite
|
Sign up to set email alerts
|

Patient and hospital factors associated with 30-day readmissions after coronary artery bypass graft (CABG) surgery: a systematic review and meta-analysis

Abstract: Background Readmission after coronary artery bypass graft (CABG) surgery is associated with adverse outcomes and significant healthcare costs, and 30-day readmission rate is considered as a key indicator of the quality of care. This study aims to: quantify rates of readmission within 30 days of CABG surgery; explore the causes of readmissions; and investigate how patient- and hospital-level factors influence readmission. Methods We conducted system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 69 publications
1
23
0
1
Order By: Relevance
“…The advantages of a shortened hospital stay might therefore be counterbalanced by preventable unplanned health care utilization, especially since planned care is not initiated until several weeks after discharge. At present, nearly 1 in 7 patients are readmitted in the first 30 days after discharge for noncardiac causes and roughly 15% of patients visit the emergency department within 1 month after CABG surgery [5][6][7][8]. It was estimated that potentially preventable readmissions following CABG surgery cost Medicare US $151 million in 2005, placing a significant burden on society [7].…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of a shortened hospital stay might therefore be counterbalanced by preventable unplanned health care utilization, especially since planned care is not initiated until several weeks after discharge. At present, nearly 1 in 7 patients are readmitted in the first 30 days after discharge for noncardiac causes and roughly 15% of patients visit the emergency department within 1 month after CABG surgery [5][6][7][8]. It was estimated that potentially preventable readmissions following CABG surgery cost Medicare US $151 million in 2005, placing a significant burden on society [7].…”
Section: Introductionmentioning
confidence: 99%
“…This was based on the available literature, and unpublished data from the NBHC, showing that frail patients have a higher risk of hospital readmission within 30 days of cardiac surgery [ 32 , 36 ]. It is generally reported that rates of readmission after cardiac surgery can range between 10–15% and are influenced largely by patient characteristics [ 37 ]. In the present pilot study, none of the patients who received THE-FACS intervention required readmission to the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…As with other acute illnesses, the postoperative period is a period of heightened vulnerability for patients, 32 particularly those with anaemia. As confirmed in this study, cardiac surgery exacerbates anaemia quite significantly postoperatively, 9,10,[33][34][35] causing haemoglobin levels to drop by an average of 30-40% and remain below 100 g/L for several weeks to months.…”
Section: Discussionmentioning
confidence: 99%